Mies: a Fighter for Film - Robbers, Lutz (Facultad de Arquitectura, Universidad Nacional Autónoma de México, 2019)
In the second part of Lutz Robbers's research on the close and not so known relationship between Mies van der Rohe and the german filmers of the Weimar Republic, we are shown his personal connection to Viking Eggeling, one of the masters of Abstract cinema, followed by an inspection of his regular trips to Dresden-Hellerau, and the author's conclusion on this traditionally ignored side of one of the fathers of modern architecture.